2021
DOI: 10.3390/su13042009
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Evolution of Multi-Group in the Process of Pedestrian Crossing Based on Evolutionary Game Theory

Abstract: The mixed traffic flow has an increasingly impact on the operation of urban traffic. To study the evolution law of multi-group behaviors in pedestrian crossing, we used the evolutionary game theory to establish a multi-group behavior evolution model for pedestrian crossing. The process of concern started from the risk perception and multi-group behavior choice. The evolutionary stability strategies, evolution trends, and factors affecting the evolutionary path of multi-group behaviors are discussed in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Research on green technology research and development mainly considers the role of enterprises as the main producers of technological products [20]. e rationality of choosing evolutionary games [21][22][23] lies in their ability to perform subject behavior analysis, which is consistent with the exploration of the choice of subject strategies in the development and application of green technologies, for example, scholars have used an evolutionary game approach to explore the dynamics of the behavior of parties involved in green buildings [24], other scholars have developed an evolutionary game model of real estate developers and consumers under different carbon tax policies to explore the impact of carbon tax policies on the choice of stakeholders in the construction industry [25]. Chen et al [26] developed two game models to explore the dynamic process of firms' choice of green innovation and the factors influencing that choice.…”
Section: Introductionmentioning
confidence: 99%
“…Research on green technology research and development mainly considers the role of enterprises as the main producers of technological products [20]. e rationality of choosing evolutionary games [21][22][23] lies in their ability to perform subject behavior analysis, which is consistent with the exploration of the choice of subject strategies in the development and application of green technologies, for example, scholars have used an evolutionary game approach to explore the dynamics of the behavior of parties involved in green buildings [24], other scholars have developed an evolutionary game model of real estate developers and consumers under different carbon tax policies to explore the impact of carbon tax policies on the choice of stakeholders in the construction industry [25]. Chen et al [26] developed two game models to explore the dynamic process of firms' choice of green innovation and the factors influencing that choice.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the first pedestrian crossing the street will comprehensively judge the situation of the intersection and implement the corresponding behavior decision, while the subsequent pedestrian crossing the street will show a judgment and understanding in conformity with public opinion or the behavior of the majority under the influence of herd mentality. Studies have shown [5] that the herd psychology can prompt pedestrians who cross the street illegally to form a temporary group and influence the decision-making of each individual in the group to make the same choice.…”
Section: Introductionmentioning
confidence: 99%